AC-DC converter and charge monitoring system for lithium ion batteries - Zhu, Ziwei (2017)
Li-ion batteries are one of the most commonly used batteries. In order to manage the batteries more efficiently, it is significant to monitor the performance parameters of the battery which provide essential data.